Effectiveness of the Creative Attitude Model in Science Learning (CASL) to Train Creative Thinking Skills for Elementary School Teacher Education Students - Julianto Julianto; Wasis Wasis; Rudiana Agustini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
Students must have superior competencies to answer the demands of 21st century skills and the Industrial Revolution 4.0, one of which is creative thinking skills. The purpose of this study was to produce a Creative Attitude in Science Learning (CASL) learning model as a valid, practical, and effective product/product as an effort to improve creative thinking skills and positive attitudes towards PGSD Science students. The development research design used refers to the development model design according to McKenny, consisting of: (1) preliminary study phase, including needs analysis, literature study, and field survey; (2) the model design phase includes model design, validation, revision; and (3) the model testing phase. The research subjects were 3 classes of the Elementary School Teacher Education study program. The data collection method used a creative thinking skills test sheet. The data analysis technique used is descriptive qualitative and quantitative. Based on the results of the study, it can be concluded that the CASL model can be used to train the creative. thinking skills of elementary school teacher education students.